Marine Algae Oligo-Carrageenans (Ocs) Stimulate Growth and Defense Responses in Terrestrial Plants - Moenne-Munoz, A (Springer New York, 2016)
Oligo-carrageenans (OCs) are obtained by acid hydrolysis of pure commercial carrageenans extracted from marine red macroalgae. OCs are constituted by around 20 units of sulfated galactose and, in some cases, anhydrogalactose units. The principal OCs are kappa, lambda, and iota, which have been observed to stimulate growth and defense responses in plants. Regarding growth stimulation effi ciency, the best effect in tobacco plants was obtained with OCs iota and kappa, in Eucalyptus globulus trees with OCs kappa and iota, and in Pinus radiata trees with OC kappa. Regarding defense stimulation efficiency, the best effect was obtained in tobacco plants with OCs lambda and iota and in Eucalyptus trees with OC kappa. OCs increased the amount of essential oils (volatile terpenoids) with potential repellent and insecticidal activities in Eucalyptus as well as the level of polyphenolic compounds with potential antimicrobial activities in tobacco plants. Regarding the mechanisms involved in growth stimulation, OCs increase net photosynthesis, basal metabolism, and cell division in tobacco plants, and in Eucalyptus and pine trees they mediate the increase in photosynthesis, C, N, and S assimilation, basal metabolism, and the level of growth-promoting hormones. Moreover, OC kappa increases ascorbate, glutathione, and NADPH syntheses, inducing a more reducing redox status; the increase in NADPH enhances thioredoxin reductase (TRR) and thioredoxin (TRX) activities which, in turn, stimulate photosynthesis, and basal and secondary metabolism in Eucalyptus trees. Similar OC-induced mechanisms may be occurring in tobacco plants and pine trees determining a reducing redox status that stimulate growth of NADH-TRR/TRX system, and most likely in other plants of agronomical and forestry importance. © Springer Science+Business Media New York 2016.